Antagonistic framing of sustainability by energy suppliers: Dissecting corporate CSR messages in a cross-cultural comparison. (1st April 2019) - Weder, Franzisca; Koinig, Isabell; Voci, Denise
Abstract : Purpose: The purpose of this paper is to determine inasmuch energy suppliers dedicate communicative resources toward sustainable development and corporate social responsibility (CSR), also paying attention to how they frame it, and if they manage to achieve consistency in their communication or fall victim to contradictions. Design/methodology/approach: By use of a qualitative content analysis, online communication tools (information on corporate websites) as well as content for download were examined in detail. The present study sample comprised of 12 case studies from selected countries (Austria, Russia, Germany, the USA, France and Korea). Findings: Overall, findings indicate that CSR has already been implemented in most energy and energy-related industries; however, it is put forward with varying degrees of attention and intensity, depending on which topics energy companies choose to address communicatively (results were classified according to a frame positioning scheme by Weder, 2012, 2018). Results underscore the fact that, at times, companies are struggling to link their CSR projects back to their core businesses. Yet, a clear trend to politicization can be described as a strong correlation of communication strategies of energy suppliers and political programs of the respective country becomes obvious. Research limitations/implications: Limited research as to how CSR topics are framed in different branches has been conducted to date; likewise, the energy sector, whose motives has been often subject to public questioning, has received little attention in CSR communication research to date. Hence, ambiguities were presumed to exist. Originality/value: The present study examines the relevance and framing of CSR in a highly competitive, centralized industry that is challenged by a global process of transition to renewable energy. The results show that the analyzed energy suppliers offer only a limited variety of issue-specific frames; instead CSR as well as sustainability are (ab)used as master frames or "buzz words" in a fairly shallow economic or socio-political argumentation.